Ferriols at Heidegger: Ang Pagbigkas sa Kasaysayan bilang Talagang Nangyayari - Pasco, Marc Oliver D (Archīum Ateneo, 2018)
This essay aims to view the philosophy of Roque J. Ferriols, from a Heideggerian perspective. It argues that Ferriols’ way of philosophizing may be appreciated by illuminating it with Heidegger’s authentically historical way of philosophizing. Heidegger’s Wiederholung or creative retrieval of Ancient Greek philosophy is evident in Ferriols’ own approach in thinking meron. Both hold that genuinely historical philosophical thinking may not be reduced to a historiographical approach to philosophizing, akin to Nietzsche’s account of the antiquarian approach to history. To wit, it may be argued that Ferriols’ way of thinking is somehow similar to Heidegger’s insofar as it desires to perform its own unique way of creatively retrieving the meaning of meron from its authentically historical roots as talagang nangyayari, as thought and lived out in the Filipino context. Ferriols’ pagbigkas sa meron resonates with Heidegger’s call to retrieve the historically forgotten meaning of Sein.